2012
DOI: 10.1002/hed.21815
|View full text |Cite
|
Sign up to set email alerts
|

Total thyroidectomy with ultrasonic scalpel: A multicenter, randomized controlled trial

Abstract: The use of an ultrasonic scalpel was as safe as that of the conventional technique and had the advantage of a shorter operative time and lower postoperative drainage. Costs were not different between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The sample sizes of the included studies ranged from 20 to 261 patients. Six studies reported cost data for thyroidectomy, 18 , 19 , 22 , 23 , 25 , 26 two studies reported data for Nissen fundoplication, 24 , 27 two studies reported data for colectomy, 20 , 28 and three studies reported data for other surgical procedures (ie, cholecystectomy, 29 pancreaticoduodenectomy, 30 and gastrectomy 21 ). In all studies, Harmonic devices were compared to conventional techniques.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample sizes of the included studies ranged from 20 to 261 patients. Six studies reported cost data for thyroidectomy, 18 , 19 , 22 , 23 , 25 , 26 two studies reported data for Nissen fundoplication, 24 , 27 two studies reported data for colectomy, 20 , 28 and three studies reported data for other surgical procedures (ie, cholecystectomy, 29 pancreaticoduodenectomy, 30 and gastrectomy 21 ). In all studies, Harmonic devices were compared to conventional techniques.…”
Section: Resultsmentioning
confidence: 99%
“…The UltraCision Harmonic Scalpel or Shears were used in seven studies, 18 – 20 , 24 , 27 – 29 the Harmonic Focus was used in three studies, 21 , 22 , 26 the Harmonic CS-14C 25 and the Harmonic Wave 30 were used in one study each, and one study did not specify the type of Harmonic device that was used. 23 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All primary studies were described as a randomized clinical trial. Of the 31 studies, only ten adequately described the randomization and allocation of patients 14,16,22,24,28,30,33,34,42,43 . In 17 studies the method of randomization was not describ ed 15,[17][18][19][20]25,26,27,29,31,32,[35][36][37][38][39]41 and in another four it was considered inappropriate 13,21,23,40 .…”
Section: Assessment Of Methodological Risk Of Primary Studiesmentioning
confidence: 99%